The effect of exercise on depressive symptoms in multiple sclerosis based on a meta‐analysis and critical review of the literature. (18th October 2014) - Dalgas, U.; Stenager, E.; Sloth, M.; Stenager, E.
<x xml:space="preserve">Abstract</x> Background and purpose The purpose of this study was to perform a systematic review of the literature on the effects of exercise on depressive symptoms in patients with multiple sclerosis (MS), as well as to apply meta‐analytical procedures to the results. Methods A systematic search covering eight databases was conducted. The included studies were randomized controlled trials applied to people with definite MS who completed a structured exercise intervention which were compared to any comparator, including other forms of exercise. The outcomes included a primary measure of depression/depressive symptoms or an instrument with a clearly defined depression subscale. Results Fifteen randomized controlled trial studies were identified including a total of 331 exercising subjects and 260 controls. The average Physiotherapy Evidence Database (PEDro) score was 5.6 ± 1.3 points. Only one study applied depressive symptoms as the primary outcome. Four studies showed positive effects of exercise on depressive symptoms. An in‐depth analysis of the studies revealed that the baseline level of depressive symptoms, patient disability level, choice of depression instrument and exercise intensity may influence the results. The meta‐analysis included 12 studies reflecting a total of 476 subjects. The standardized mean difference across studies was g = −0.37, 95% confidence interval (−0.56; −0.17), and the null hypothesis of homogeneity within the sample could not be rejected (Q = 12.05, df = 11, P = 0.36). Discussion Exercise may be a potential treatment to prevent or reduce depressive symptoms in individuals with MS, but existing studies do not allow solid conclusions. Future well‐designed studies evaluating the effects of exercise on depressive symptoms and major depression disorder in MS are highly warranted.